2019
DOI: 10.1080/21645515.2018.1554972
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-HBs persistence after hepatitis B vaccination on two-dose schedule and three-dose schedule among adults: results from a 12-year follow up study in China

Abstract: Comparison of anti-HBs persistence after hepatitis B vaccination on two-dose schedule and three-dose schedule among adults is still controversial. In this study, adults were followed up at 12 years after the primary immunization. Three hundred and forty-one and 288 adults with age 15 through 40 years old were given anti-HBV vaccination on a 0-, 1-, and 6-month schedule or on a 0-and 6-month one, respectively (in 2003). Blood samples of 202 patients on 0-, 1-and 6-month schedule and 194 patients on 0-and 6-mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The proportion of participants whose anti-HBs remained positive twelve months after being fully vaccinated increased with the increase of initial concentration one month after being fully vaccinated, which meant that higher anti-HBs concentrations are associated with longer protection duration. It was considered to be consistent with previous studies [31,36,37]. Moreover, this study suggests that subjects with a low anti-HBs concentration at the primary response should be carefully followed up.…”
Section: Discussionsupporting
confidence: 90%
“…The proportion of participants whose anti-HBs remained positive twelve months after being fully vaccinated increased with the increase of initial concentration one month after being fully vaccinated, which meant that higher anti-HBs concentrations are associated with longer protection duration. It was considered to be consistent with previous studies [31,36,37]. Moreover, this study suggests that subjects with a low anti-HBs concentration at the primary response should be carefully followed up.…”
Section: Discussionsupporting
confidence: 90%
“…It is a safe and efficient measure that is available in the Brazilian National Health System, and it is free of charge for all citizens 5 . The vaccine is intramuscularly administered in three doses at 0, 1, and 6 months, and immunization can be achieved after completing the vaccination schedule in 90% to 95% of the cases 6 . Thirty days after the third dose, it is important to confirm the development of immunity by testing for the presence of anti-HBs antibodies in the organism 7 .…”
mentioning
confidence: 99%
“…It was observed that the anti-HBs test showed a positive result in most of the participants, although there were a significant number of individuals who presented negative results despite completing the vaccination scheme. It should be noted that completing a full vaccination schedule does not guarantee immunity against HB in the individuals, as they can remain exposed to the risks of infection 6 . This condition may occur due to inadequate administration of the vaccine, inadequate time intervals between doses, and individual factors such as smoking, obesity, renal failure, immunosuppression, and hepatic diseases 10 .…”
mentioning
confidence: 99%
“…26,27 Previous studies have documented that immune persistence after HepB vaccination in children may be positively correlated with higher peak concentrations of HBsAb after primary immunization. 3,4,8,10,13 Although the difference in seropositivity rate is often not statistically significant, there is increasing evidence supporting lower levels of HBsAb after the primary three-dose HepB vaccination in preterm infants compared to full-term infants. 12 Therefore, the assumption that immune persistence after HepB vaccination in preterm infants is lower than that of full-term infants seems quite reasonable.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have revealed that the long-term protection provided by the full primary course of HepB is sufficient to prevent HBV infection in immunologically competent persons for at least 20 years and concluded that additional booster doses are not necessary. [5][6][7] Existing studies on the immune persistence of HepB have primarily focused on specific populations or special strategies, such as haemodialysis patients, 8 HIV-infected patients, 9 comparisons between twodose and three-dose schedules, 10 and the persistence of HepB in adults. 11 A meta-analysis found that preterm birth (PTB) children had a significantly poorer immune response to HepB compared to full-term children, with a 1.36 times greater risk of non-response compared to the full-term group.…”
Section: Introductionmentioning
confidence: 99%